Report of the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) 2007 - United Nations Scientific Committee on the Effects of Atomic Radiation (United Nations, 2007)
Official Records of the Report of the United Nations Scientific Committee on the Effects of Atomic Radiation, Fifty-fifth Session (21-25 May 2007).